Восход над океаном: [роман] / К. Лонг - Лонг Китти (Панорама романов о любви, 2005)
Экземпляры: ЧЗ (20181122) / Инвентарный номер: 39993 / Цена: 30 / Сис.шифр: Р2 / Авт.знак: Л 76 / ГРНТИ: 17.82.31 / ББК: 84(4Вел)